One-shot high-resolution melting curve analysis for KRAS point-mutation discrimination on a digital microfluidics platform. Issue 3 (14th December 2021) - Li, Mingzhong; Wan, Liang; Law, Man-Kay; Meng, Li; Jia, Yanwei; Mak, Pui-In; Martins, Rui P.
Abstract : Proposed high-accuracy one-shot melting curve analysis on a digital microfluidics platform, enabling KRAS gene discrimination with single-nucleotide mutations in 3 seconds. Abstract : Single-nucleotide polymorphism (SNP) plays a critical role in personalized medicine, forensics, pharmacogenetics, and disease diagnostics. Among different existing SNP genotyping techniques, melting curve analysis (MCA) becomes increasingly popular due to its high accuracy and straightforward procedures in extracting the melting temperature ( T m ). Yet, its study on existing digital microfluidic (DMF) platforms has intrinsic limitations due to the temperature inhomogeneity within a thickened droplet during the on-chip rapid heating process. Although the utilization of an on-chip thermostat can regulate and monitor the dynamic melting process in real time, the limited T m accuracy resulting from the insufficient system response time to accommodate the fast-melting evolution still poses a great challenge for precise MCA with high throughput. This work proposes a one-shot MCA on a DMF platform. The tailoring of a functional substrate with hierarchical micro/nano structure enables high-resolution patterning of pL-scale droplets. Specifically, the hydrothermal and photocatalysis treatment allows the functional substrate to exhibit a superwettability contrast of >170°, facilitating passive isolation of the pL-scale DNA sample into highly-resolved pL droplets above the 200 μm superhydrophilic patterns. This high-resolution MCA technique can successfully discriminate KRAS gene targets with single-nucleotide mutations in 3 seconds. The high accuracy and consistency in the acquired T m when compared with off-chip results demonstrate its opportunities for near-patient diagnostics, precision medicines, genetic counseling, and prevention strategies on DMF platforms.